Background and analysis of the teaching of science and technology: towards a third culture - Castaño Tamara, Ricardo (Visión electrónica, 2014)
In the current questions about ¿ What are the purposes of science education?, teaching of science and technology must always seek to answer accurately considering the social issues involved in the scientific-technological complex. As such, this article is part of the background of the research project in the Inter advance Doctorate in Education from the University Francisco Jos´e de Caldas (DIE-UD), space training Education and Pedagogy of the thesis : Angelus novus: analysis of the vision of the academicians on progress and techno-science from critical theories. It then aims to develop key aspects of the background to the vision of teachers of science and technology; exhibit some perception studies of science and technology; make a brief tour of the visions that arise about the nature of technological activity; and finally present an approach to the third culture that seeks to bring together scientists and humanists towards a more comprehensive understanding of developments in science and technology today.